2010
DOI: 10.1097/01.hp.0000346796.30582.64
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Co2 - Radical Formation in Biological and Synthetic Apatites

Abstract: Biological apatites (tooth enamel, bone) and their synthetic analogues were exposed to gamma rays, UV light, or thermal treatment and studied by electron paramagnetic resonance (EPR). The thermal generation of CO2- radicals in synthetic apatite was observed for the first time. It was shown that the experimental EPR spectra of all of the above-mentioned materials are caused by the contribution of two types of CO2- radicals: axial and orthorhombic. The ratio of their concentrations depends on the characteristic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…In case of shrimp shell CO2 radical was found to be trapped in the structural polysaccharide of shrimp exoskeleton and probably originated from the available organic matter like amino sugar, a major component of chitin (Desrosiers, ). Rudko et al () reported that the EPR spectrum of gamma‐irradiated hydroxyapatite is mainly caused by two types of paramagnetic centers, one is axially symmetric CO2 and the other is immobilized in the lattice defect having orthorhombic symmetry. But in case of irradiated shrimp the spin Hamiltonian parameters obtained during simulation of radiation‐induced radical ion were g ⊥ = 2.0045, g || = 1.997 with Δ B pp =0.51 indicating axially symmetric CO2 paramagnetic center.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In case of shrimp shell CO2 radical was found to be trapped in the structural polysaccharide of shrimp exoskeleton and probably originated from the available organic matter like amino sugar, a major component of chitin (Desrosiers, ). Rudko et al () reported that the EPR spectrum of gamma‐irradiated hydroxyapatite is mainly caused by two types of paramagnetic centers, one is axially symmetric CO2 and the other is immobilized in the lattice defect having orthorhombic symmetry. But in case of irradiated shrimp the spin Hamiltonian parameters obtained during simulation of radiation‐induced radical ion were g ⊥ = 2.0045, g || = 1.997 with Δ B pp =0.51 indicating axially symmetric CO2 paramagnetic center.…”
Section: Resultsmentioning
confidence: 99%
“…In case of irradiated hydroxyapatite lattice the intensity of radiation‐induced CO2 radical showed 15% enhancement during storage possibly because of the transient signals (Sholom, Haskel, Hayes, Chumak, & Kenner, ). These transient signals were associated with the mechanism of CO2 formation and disappeared in the gamma‐irradiated enamel after 1 month of storage at room temperature or after annealing for 1 hr at 90°C (Rudko et al, ). The irradiated shrimp exhibited complete removal of axially symmetric CO2 signal when subjected to thermal treatment at greater than 80°C.…”
Section: Resultsmentioning
confidence: 99%
“…The free electrons originate from impurities in the hydroxyapatite crystals by ionizing radiation or temperature (while this might not be as common as ionizing radiation, temperature increases resulting from interactions with ionizing radiation can lead to thermal ionization or thermally induced chemical reactions that produce free radicals) when tooth enamel is exposed to ionizing radiation (Rudko et al 2010). Therefore, when the hydroxyapatite crystals absorb ionizing radiation, the carbonate ion (CO 3 2– ) located in hydroxyl (A site) and phosphate (B site) of the hydroxyapatite lattice and the neutral CO 2 mol ecule on the surface of crystallites absorbs the free electrons that originate from the ionization of impurities (i.e., secondary thermalized electrons) in the hydroxyapatite and form the • CO 2 − radical anions as shown in (eqn) 1 and 2.…”
Section: Fundamentals Of Epr Dose Reconstruction In Tooth Enamelmentioning
confidence: 99%
“…Additionally, tooth enamel is a highly stable component of a tooth whose composition does not change with aging as opposed to bones (Wieser et al 2000). When tooth enamel is exposed to ionizing radiation, the carbon dioxide radical anions ( • CO 2 – ) are generated by ionizing radiation from a neutral carbon dioxide (CO 2 ) molecule on the surface of crystallites, and the bulk carbonate (CO 3 2– ) impurities present in the hydroxyapatite crystals (Rudko et al 2010; Moens et al 1993). The free radicals in tooth enamel are extraordinarily stable for about 10 million (10 7 ) years at normal temperature (25 °C) and pressure (Hennig et al 1981), which makes tooth enamel an 'ideal dosimeter' for both retrospective and accident dosimetry studies; it detects radiation exposures independent of the time of occurrence (Wieser et al 2000).…”
Section: Introductionmentioning
confidence: 99%